Pengaruh Penerapan Pelaporan Keuangan Berbasis Extensible Business Reporting Language (XBRL) terhadap Ketepatan Waktu Pelaporan Keuangan: Studi Empiris pada Perusahaan BUMN di Bursa Efek Indonesia Periode 2019-2022 - Putri, Rizquita Istighfarinda; Setiawan, Mia Angelina (Jurnal Nuansa Karya Akuntansi, 2024)
This research aims to analyze the impact of implementing XBRL in financial reporting on the timeliness of submitting financial reports by controlling the DER and ROA variables. The population of this research is state-owned companies listed on the Indonesia Stock Exchange for the period 2019 to 2022. The research sample consists of 25 companies or a total of 100 years of observations. The sample selection technique in this research used the purposive sampling method. Data analysis used logistic regression which was processed using SPSS version 26 software. The research results showed that XBRL had a positive effect on the timeliness of submitting financial reports, although not significantly. The same applies to the Debt-to-Equity Ratio variable used to control the company's debt level, which has a positive but insignificant effect. The Return on Asset variable, which is used to measure company profitability, has a positive and significant influence on the timeliness of submitting financial reports for state-owned companies listed on the Indonesia Stock Exchange.